Effect of treatment mode on fatigue resistance of material and thickness of the hardened surface - Желдубовский, Александр Владимирович; Сердитов, Александр Тимофеевич; Ключников, Юрий Валентинович; Кондрашев, Павел Васильевич; Моисеенко, Глеб Сергеевич (Eastern-European Journal of Enterprise Technologies, 2014)
The vast majority of modern machine parts operate under cyclic loads, leading to, as a rule, failure, caused by the material fatigue. In this regard, the fatigue resistance of materials is one of the most important criteria for evaluating the structural strength of many parts of engineering structures. It is important that the process of exhaustion of cyclic life of metals, even at uniform stress state proceeds not uniformly in terms of volume of metal, but is initiated and develops more intensively in its surface layer. Under non-uniform stress state, role of the surface increases in connection with the presence of stress gradient. That's why, the most profound and systematic summarization of works, carried out in this direction, is aimed at performing a comprehensive analysis of changes in the properties of the surface layer of materials under active loading. However, investigated patterns of the surface microhardness change in the process of fatigue are usually qualitative and informative in nature. However, it should be noted that it is relevant to conduct studies, intended for obtaining quantitative estimates of the mentioned laws in order to develop fatigue failure criteria as a basis for improving calculation methods. This, in turn, requires developing a methodology for studying the surface layer behavior features and selecting the appropriate instrumental methods and tools. Analysis of a priori information indicates the need to investigate the microhardness, taking into account formation laws of the hardened surface layer, using different technological modes of surface treatment of metallic materials. In the present paper, the microhardness measuring method, characterized by a fairly high level of reproducibility of the obtained results and their experimentally justified correlation with the mechanical properties of the material is used. The developed method allows to determine the parameters of realized and residual life of the material. Thus, the research results, presented in the paper are of both scientific and practical interest. The authors have proposed the microhardness measuring methodology, characterized by a high level of reproducibility of the obtained results, which allows to determine the parameters of realized and the residual life of the material.